(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Objective: To assess the serum concentrations of vitamin D and calcium and bone mineral density (BMD) in patients with juvenile idiopathic arthritis (JIA) and to compare them with those of healthy children. Patients & Methods: A total of 75 JIA children were evaluated and compared to healthy individuals matched for age and sex in this cross-sectional case-control study. Laboratory evaluations included serum calcium and 25-hydroxyvitamin D. The normal range of serum calcium was 9-11 mg/dl; vitamin D was classified as normal (>32 ng/ml), insufficient (20-32 ng/ml), and deficient (<20 ng/ml). BMD was assessed by dual-energy X-ray absorptiometry (DXA) of the lumbar spine and both femur necks. BMD (in g/cm²) was expressed in Z score, the number of standard deviations above or below the mean value of an age- and sex-matched reference population. In children, low bone mass was defined as a Z-score equal or less than minus 2 (-2). Results: The mean vitamin D level in both cases and controls was low, which was 18.66 ± 10.22 and 21.3 ± 4.07, respectively. Vitamin D deficiency and insufficiency in JIA patients were 69.3% and 21.3%, respectively. The mean concentration of serum calcium of cases was 9.46±0.46 mg/dl. Low bone mass in JIA patients’ lumbar, right femur, and left femur was found in 97.3%, 69.3%, and 70.7%, respectively (p < 0.001, 0.023, 0.016). All types of JIA had low bone mass in lumbar vertebrae. BMD Z-scores in the right and left femoral necks showed a significant correlation with types of JIA (p=0.007 and 0.035, respectively). There was no significant association between disease duration and vitamin D or BMD at any sites in our study. Conclusion: The study indicated that hypovitaminosis D and low bone mass are common in JIA patients and healthy controls in Bangladesh. It highlights the need to enhance dietary intake of calcium and vitamin D, along with promoting physical activities and sunlight exposure for JIA patients. Bangladesh J. Nuclear Med. 28(2): 321-328, July 2025